Factors Associated with Hepatitis B and Hepatitis C among Infected Patients in Indonesia and Their Knowledge and Attitude: A Multicenter Observational Study - Juferdy Kurniawan; Gita Aprilicia; Hery Djagat Purnomo; Cecilia O Permatawedi; Ulfa Kholili; Tehar Karo-Karo; Haris Widita; Aritantri Darmayani; Arif Nur Widodo; Nenny Agustanti; Saptino Miro; Suyata Suyata; et al. (Interna Publishing, 2024)
Background: Hepatitis B virus (HBV) and Hepatitis C virus (HCV) infections are global health problems, including in Indonesia. The purpose of this study was to assess the knowledge and attitudes about HBV and HCV infection among infected patients in Indonesia. Methods: This cross-sectional study used a questionnaire survey. The questionnaire was adapted and translated into Indonesian language, and trialed with 27 HBV and 27 HCV patients. The final validated questionnaire was later used in the target population. Patients diagnosed with Hepatitis B or Hepatitis C were included. The patients were enrolled from November 2019 until February 2020 in sixteen multicenter locations. Multivariate analysis with logistic regression was conducted to determine the factors that are associated with the knowledge and attitude among HBV and HCV patients toward their illness. Results: A total of 931 HBV patients and 254 HCV patients were included in this survey. The proportion of infected patients with adequate knowledge of Hepatitis B and Hepatitis C was 72.1% and 53.9%, respectively. Positive attitudes about Hepatitis B and Hepatitis C were 28.5% and 41.3%, respectively. Multivariate analysis revealed that higher education level, higher income level, diagnosis duration of more than 5 years, and receiving of antiviral therapy were independent factors associated with adequate knowledge about Hepatitis B among HBV patients. Among HCV patients, independent factors associated with adequate knowledge about Hepatitis C were being married, higher education level, higher income level, and receiving antiviral therapy. Moreover, older age and receiving of antiviral therapy were independent factors associated with positive attitudes towards Hepatitis B among HBV patients. However, only higher education level was found to be an independent factor associated with positive attitudes towards Hepatitis C among HCV patients. Conclusion: The knowledge and attitude of patients regarding HBV and HCV were quite low among infected patients in Indonesia.